Childhood adversity and traumatic exposures during deployment as predictors of mental health in Australian military veterans. (29th December 2015) - Zheng, Wu Yi; Kanesarajah, Jeeva; Waller, Michael; McGuire, Annabel C.; Treloar, Susan A.; Dobson, Annette J.
Abstract: Objective : To examine whether the relationship between traumatic exposure on deployment and poor mental health varies by the reported level of childhood adversity experienced in Australian military veterans deployed to the Bougainville or East Timor military operations. Methods : Cross‐sectional self‐reported survey data were collected in 2008 from 3, 564 Australian military veterans who deployed to East Timor or Bougainville on their deployment experiences, health and recall of childhood events. Multivariable logistic regression was used to investigate the association between childhood adversity, deployment exposures and mental health. Results : The most common childhood adversity reported was 'not having a special teacher, youth worker or family friend who looked out for them while growing up'. On average, responders reported experiencing 3.5 adverse childhood experiences (SD 2.7) and averaged 5.3 (SD 4.9) traumatic exposures on deployment. Both childhood adversity and traumatic exposures on deployment were associated with higher odds of poorer mental health. However, there was no evidence that level of childhood adversity modified the association between traumatic exposure and mental health. Conclusions/Implications : These findings suggest that military personnel who recalled a higher level of childhood adversity may need to be monitored for poor mental health and, if required, provided with appropriate support.